High‐Pressure Synthesis of Metal–Inorganic Frameworks Hf4N20⋅N2, WN8⋅N2, and Os5N28⋅3 N2 with Polymeric Nitrogen Linkers. (8th May 2020) - Bykov, Maxim; Chariton, Stella; Bykova, Elena; Khandarkhaeva, Saiana; Fedotenko, Timofey; Ponomareva, Alena V.; Tidholm, Johan; Tasnádi, Ferenc; Abrikosov, Igor A.; Sedmak, Pavel; Prakapenka, Vitali; Hanfland, Michael; et al.
Abstract: Polynitrides are intrinsically thermodynamically unstable at ambient conditions and require peculiar synthetic approaches. Now, a one‐step synthesis of metal–inorganic frameworks Hf4 N20 ⋅N2, WN8 ⋅N2, and Os5 N28 ⋅3 N2 via direct reactions between elements in a diamond anvil cell at pressures exceeding 100 GPa is reported. The porous frameworks (Hf4 N20, WN8, and Os5 N28 ) are built from transition‐metal atoms linked either by polymeric polydiazenediyl (polyacetylene‐like) nitrogen chains or through dinitrogen units. Triply bound dinitrogen molecules occupy channels of these frameworks. Owing to conjugated polydiazenediyl chains, these compounds exhibit metallic properties. The high‐pressure reaction between Hf and N2 also leads to a non‐centrosymmetric polynitride Hf2 N11 that features double‐helix catena‐poly[tetraz‐1‐ene‐1, 4‐diyl] nitrogen chains [−N−N−N=N−]∞ . Abstract : A one‐step high‐pressure synthetic route is used to complex metal–inorganicframeworks built of transition metals(Hf, Os, and W) that are connected via polymeric nitrogen linkers. The pores are filled with ordered one‐dimensional arrays of nitrogen molecules. Owing to the conjugated π‐systems, these inorganic polymers are conductive materials.